2021
DOI: 10.1126/sciadv.abe7204
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial screen of dynamic mechanical stimuli for predictive control of MSC mechano-responsiveness

Abstract: Mechanobiological-based control of mesenchymal stromal cells (MSCs) to facilitate engineering and regeneration of load-bearing tissues requires systematic investigations of specific dynamic mechanical stimulation protocols. Using deformable membrane microdevice arrays paired with combinatorial experimental design and modeling, we probed the individual and integrative effects of mechanical stimulation parameters (strain magnitude, rate at which strain is changed, and duty period) on myofibrogenesis and matrix p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Multivariate optimization methods were employed to obtain the optimal conditions. 26 Firstly, different types of ALG and pectin must be selected, which might influence the physical and chemical properties of the produced hydrogel carrier. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate optimization methods were employed to obtain the optimal conditions. 26 Firstly, different types of ALG and pectin must be selected, which might influence the physical and chemical properties of the produced hydrogel carrier. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While several recent studies have provided alternative approaches to actuating their bioreactors, the constructs lack physiologic relevance given that these systems largely rely on uniaxial loading, involve tissue constructs that are not representative of an anatomic location for the tissue construct to be used in and offer inadequate mechanical load to tissue constructs. The diaphragm pump and pressure regulator system used in Liu et al's study allowed for the tissue construct to receive compressive mechanical stimulation by cyclic bulging and deformation of the membrane the tissue was cultured upon [ 64 ]. Raimondi et al proposed a bioreactor which provided pulsatile shear stress and uniaxial tensile loading using an electromagnetic actuator.…”
Section: Conventional Tendon Tissue Engineeringmentioning
confidence: 99%
“…With longer experiments, it would also be beneficial to explore the effect of incrementally increasing loading throughout the culture. It has been shown that incremental loading is necessary for sustained improvement in the mechanical properties of MSK tissues [ 64 ]. The capability of the humanoid robot presented in Mouthuy et al's study to offer multiple force loading regimes consistent with estimated quantities of force in human tendon during abduction is promising for the eventual development of physiologically relevant tissue constructs [ 87 – 90 ].…”
Section: Advanced Robotics For Provision Of Mechanical Loadingmentioning
confidence: 99%
“…It was hypothesized that the increase in stress-strain was due to the increased covalent bonds provided by CS, as shown in the results above. The mechanical properties of scaffolds are known to affect cellular functions, extracellular matrix remodeling, and cellular differentiation [39]. In addition, the increase in tensile stress-strain allows for better manipulation during surgery and for better adaptation to native pressures.…”
Section: Synthesis and Characterization Of The Cs/gelma Scaffoldmentioning
confidence: 99%